Two new species of endophytes (ascomycetes) from Zingiberaceae sporulating in culture - Bussaban B. (2014)
Gaeumannomyces amomi sp. nov. (Magnaporthaceae inc. sed.) was isolated from healthy leaves and pseudostems of Alpinia malaccensis and Amomum siamense, while Leiosphaerella amomi sp. nov. (Hyponectriaceae) was isolated from leaves, pseudostems, and rhizomes of these plants. All plants were collected in Doi Suthep Pui National Park, Chiang Mai, Thailand. Both taxa were isolated following a standard triple sterilization treatment for endophytes. The new taxa are described, illustrated and compared with species of Curvatispora, Gaeumannomyces, Lanceispora and Leiosphaerella. This is the first time that species of Gaeumannomyces and Leiosphaerella have been found as endophytic fungi in the Zingiberaceae.